Explaining Positional Voting Paradoxes II: The General Case - Donald G. Saari (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
A theory is developed to explain all possible positional voting paradoxes coming from a single but arbitraily chosen profile. This includes all pairwise voting cycles, all conflict between Borda and Condorcet winners and rankings, all disagreement in outcomes among positional procedures, and all discrepencies among rankings for any positional procedure as candidates are dropped or added. The theory explains why each of the possible paradoxes occurs while describing how to construct illustrating profiles. It is shown how to use this approach to derive properties of other procedures based on positional voting methods. The three candidate results of the companion paper [19] are extended to an arbitrary number of candidates.
Keywords: 330